(untitled) (CAHIERS MAGELLANES-NS, 2024)
The Ceramic waste is generated in large quantity during manufacturing process of tiles and other ceramic products. These creates many hazards to both environment and human being. The development of High-Performance Concrete is essential requirement of construction industry without harming the environment and Mechanical properties of concrete. Metakaolin is also one of waste material which possesses good physical and chemical properties. The Ceramic waste and Metakaolin have been incorporated in this experimental study as a partial replacement of cement. The Metakaolin helps concrete to protect against alkali silicate reaction and sulphate attack. It is widely used mineral admixture with concrete. This study is based on trial and error approach with various proportion of ceramic waste and metakaolin as a replacement. The percentage of ceramic waste is taken constant and variation is allowed in percentage of Metakaolin.